PREFERENSI MASYARAKAT KOTA MEDAN TERHADAP BANK SYARIAH - Dewi Andriani, Azuar Juliandi (Jurnal Riset AKuntansi dan Bisnis, 2008)
Sharia bank now has popularity among the people of Indonesia. Sharia bankbased on present Islamic economic principles. Sharia Bank has a big role increaseworld banking in Indonesia. Attentive Indonesia society majority is Moslem, soSharia Banking in the future has good prospect with increase knowledge aboutawareness to use banking produc and information with experience society aboutbenefit sharia banking. This study aimed to know knowledge and attitude society forsharia banking and to know knowledge and attitude for decision receive shariabanking. Survey methods applied in this research.The research is gathered using a questionnaire randomly distributed tocustomers as much as 100 the respondents. Data are analyzed using descriptive andkuantitative analysis techniques. Based on the results of the analysis conclusionscan be drawn that Medan society knowledge good enough, Medan society attitudegood enough, and any relation positive and significant society knowledge andattitude with decision receive for sharia banking.